Elephant warning system using IOT - M, Radhika.; Nashreen.Z, Rahamathun; Lakshmi Sravya, Vinjam (International Journal of Engineering and Technology, 2018)
India is a nation of Mega-Diversity.There are large number of plants and wild animals.One of the most common problem India which is facing today is the wildlife conflicts.There are several areas and farms which are more in risk to wildlife attacks. Elephant crop raiding is very common in most of these places. An average of 250 human death by elephants are reported from India. In this paper we have tried to give a digital solution with the help of the popular Internet of Things which can give an awareness or warning to the local people about the movement of elephants in forest areas by detecting the infrasound communication of elephants. The warning will be given by an android based application.Â Â